Diet analysis of Clithon retropictum in south coast of Korea using metabarcoding - Hwang, Soonwon; Cho, Kwangjin; Han, Donguk; Back, Yonghae; Lee, Eunjeong; Park, Sangkyu (Journal of Ecology and Environment, 2024)
Background: This study focused on the diet of Clithon retropictum, level II endangered species in Korea. Since the development of brackish water zones has led to a decline in the population of this species, to obtain information on the ecology of C. retropictum required for its conservation and restoration. To investigate the actual preys of C. retropictum in south coast of Korea, we conducted high-throughput sequencing and metabarcoding techniques to extract DNA from gut contents and periphyton in their habitats. Results: Total 118 taxonomic groups were detected from periphyton samples. 116 were Chromista and Cyanobacteria dominated in the most samples. In gut contents samples, 98 taxonomic groups were detected. Similar to the results of periphyton, 96 were Chromista and Cyanobacteria dominated in the most samples. In the principal component analysis based on the presence/absence of taxonomic groups, gut content composition showed more clustered patterns corresponding to their habitats. Bryophyta was the most crucial taxonomic group explaining the difference between periphyton and gut contents compositions of C. retropictum. Conclusions: Our finding suggests that C. retropictum may not randomly consume epilithic algae but instead, likely to supplement their diet with Bryophyta.
Keywords: brackish water zone; Clithon retropictum; diet analysis; gut contents; metabarcoding